What is parallax? - OER project materials - Hardegree-Ullman, Emily, filmmaker (Colorado State University. Libraries, 2020)
This video demonstrates the concept of parallax and its utility for measuring cosmic distances.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: cosmic distance ladder; parallax; parsec; Open educational resources